ANALISIS TUTUPAN VEGETASI MANGROVE DI PULAU MANTEHAGE, TAMAN NASIONAL BUNAKEN, SULAWESI UTARA - Sapsuha, Jufran; Djamaluddin, Rignolda; Sondak, Calvyn F.A.; Rampengan, Royke M.; Opa, Esri T.; Kambey, Alex D. (Sam Ratulangi University, 2018)
Mangrove forest are typical forest growing on along coasts, river mouth saffected by tides. This study was conducted on April to September 2018 in Mantehage Island, Bunaken National Park, North Sulawesi. It was aimed to evaluate vegetation cover change during the period from 1995 to 2017 and to deskrip condition of mangrove vegetation at locations where the vegetation covers were identified to have been change. Image interpretation method and ground checks were applied in the study. RGB composite results of 473 1995 Landsat-5 images, RGB 453 of Landsat-7 images in 2005 and RGB 564 of Landsat-8 images in 2017 showed the area of mangrove vegetation cover in 1995, 2005 and 2017 respectively were 1333.95 ha, 1371.53 and 1383.21 ha. There was an increase in the area of mangrove vegetation cover in 1995-2005 covering an area of 37.58 ha and in the years 2005-2017 covering an area of 11.68 ha. In total there was an additional vegetation cover change of 49,26 ha for 22 years. Result from ground check indicated that the change in vegetation covers occurred at locations subjected to sedimentation, natural recovery at previous clear-cutting areas and area of artificial plantation. The phenomenan of mangrove diebach was found in the middle part between the two mainlands of Mantehage Island.Hutan mangrove merupakan tipe hutan yang khas dan tumbuh di sepanjang pantai atau muara sungai yang dipengaruhi oleh pasang surut air laut. Penelitian ini dilakukan dari bulan April-September 2018 di Pulau Mantehage, Taman Nasional Bunaken, Sulawesi Utara dengan tujuan untuk mengevaluasi perubahan tutupan vegetasi mangrove di Pulau Mantehage dengan selang waktu 1995, 2005 dan 2017sertaMendeskripsikan kondisi vegetasi mangrove yang teridentifikasi mengalami perubahan tutupan. Penelitian dilakukan dengan metode interpretasi citra dan survei lapangan (Ground check). Hasil komposit RGB 473 citra Landsat-5 tahun 1995, RGB 453 citra Landsat-7 tahun 2005 dan RGB 564 citra Landsat-8 tahun 2017 menunjukkan luas tutupan vegetasi mangrove pada tahun 1995, 2005 dan 2017 secara berturut-turut adalah 1333,95 ha, 1371,53 dan 1383,21 ha. Terjadi penambahan luas tutupan vegetasi mangrove pada tahun 1995-2005 seluas 37,58 ha dan pada tahun 2005-2017 seluas 11,68 ha, jika dijumlahkan dalam kurun waktu 22 tahun terjadi penambahan luas tutupan vegetasi mangrove sebesar 49,26 ha. Hasil Ground Check di lapangan menunjukkan penambahan luas tutupan vegetasi mangrove terjadi pada lahan yang mengalami sedimentasi, lahan terbuka bekas penebangan yang mengalami pemulihan kembali dan pada lokasi tertentu yang ditanami secara artifisial. Fenomena mangrove dieback ditemukan di lokasi bagian tengah antara dua daratan Pulau Mantehage.